Review on Patents about Magnetic Localisation Systems for in vivo Catheterizations - Placidi, Giuseppe; Franchi, Danilo; Maurizi, Alfredo; Sotgiu, Antonello (Recent Patents on Biomedical Engineering (Discontinued), 2009)
in vivo Catheterizations are usually performed by physicians using X-Ray fluoroscopic guide and contrastmedia. The X-Ray exposure both of the patient and of the operators can induce collateral effects. The present review describes the status of the art on recent patents about magnetic position/orientation indicators capable to drive the probe during in-vivo medical diagnostic or interventional procedures. They are based on the magnetic field produced by sources and revealed by sensors. Possible solutions are: the modulated magnetic field produced by a set of coils positioned externally to the patient is measured by sensors installed on the intra-body probe; the magnetic field produced by a thin permanent magnet installed on the intra-body probe is measured by magnetic field sensors positioned outside the patient body. In either cases, position and orientation of the probe are calculated in real time: this allows the elimination of repetitive X-Ray scans used to monitor the probe. The aim of the proposed systems is to drive the catheter inside the patient vascular tree with a reduction of the X-Ray exposure both of the patient and of the personnel involved in the intervention. The present paper intends also to highlight advantages/disadvantages of the presented solutions.
Keywords: X-Ray exposure reduction